Educação do Emílio em Jean-Jacques Rousseau: investigação sobre uma pedagogia para a docência de filosofia no Ensino Médio - CORVÊLO, Edilene Pereira Boaes (2019)
The aim of this work is to analyze the link between philosophical thinking and teaching in two ways: the scope of philosophical-political reflection with the educational purpose of man (Rousseauian idea), and the philosophical formation desired. Faced with these presuppositions, there is the visibility of a Philosophy whose practice is pedagogy to form the citizen. An allusion to the thought of Rousseau in his Emilio or Education, to form the young for the exercise of a way of thinking that is autonomous and free in its possibilities. From the theoretical perspective of the Geneva philosopher, to analyze and describe his conception of education as a process and reference in the question of education, if one is educated for life or not, in Rousseau's perspective of negative education. The Genevan philosopher believed that the educator / preceptor should let the child depart from his own nature, from a well-governed freedom. The research was carried out with the professors (sample group) of the Higher Education Philosophy of Alcântara-MA, in the schools of the State Network and in the IFMA / Campus-Alcântara-MA, having as methodology, descriptive-quantitative, from field research, being based on interviews structured and questionnaires developed in the search to identify if the Rousseauian theory has a significant resonance in the way of teaching of the educator and reinforces the autonomy of the student.